DETERMINAN TERJADINYA FRAUD DI INSTITUSI PEMERINTAHAN - Apriadi, Rangga Nuh; Fachriyah, Nurul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The purpose of this study is to determine the effect of suitability of compensation, effectiveness of internal controls system and organization's ethical culture to the fraud in the government institution. The dependent variabel used in this study is fraud in the government institution. Independent variable used in this study are suitability of compensation, effectiveness of internal controls system and organization's ethical culture. This study used 105 respondent of Audit Board of Republic Indonesia auditors at Representative office of Jawa Timur with convenience sampling method. The method of analyzing data used is multiple linier regresion. From the regresion analysis it is found that suitability of compensation, effectiveness of internal controls system and organization's ethical culture effect fraud in the government institution. Keyword : Fraud in the government institution, suitability of compensation, effectiveness of internal controls system and organization's ethical culture